PENERAPAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP DALAM UPAYA PENEGAKAN HUKUM LINGKUNGAN DI INDONESIA - Trie Krisnasari, Komang; Mertha, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013)
The emergence of a variety of environmental cases, likely caused by human activityitself. It is needed the laws govern all things related to the environment, the related ActNumber 32 of 2009, the Protection and Environmental Management. The problems thatarise: first, what kind of law enforcement that regulated under Law no. 32 of 2009 inorder to preserve the environment in Indonesia, second what are the obstacles theenforcement of environmental law in Indonesia. The method of this research is anempirical legal research using engineering studies document the legal materialsrelevant to this issue. Conclusions from the research indicate that Law No. 32 of 2009provides three different aspects of environmental law enforcement which areenforcement administrative, civil and criminal. The constraints and obstacles in theenforcement of environmental law is from legal factors itself, law enforcement factors,facilities, constraints of communities, and natural bamers such as: volcano eruption,floods, and landslide.
Keywords: Environment, Environmental Law Enforcement, Protection, Environmental Management